2016
DOI: 10.1186/s12967-016-1082-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the touchscreen-based Muse™ Auto CD4/CD4% single-platform system for CD4 T cell numeration in absolute number and in percentage using blood samples from children and adult patients living in the Central African Republic

Abstract: BackgroundThe new microcapillary and fluorescence-based EC IVD-qualified Muse™ Auto CD4/CD4% single-platform assay (EMD Millipore Corporation, Merck Life Sciences, KGaA, Darmstadt, Germany) for CD4 T cell numeration in absolute number and in percentage was evaluated using Central African patients’ samples compared against the reference EC IVD-qualified BD FACSCount (Becton–Dickinson, USA) flow cytometer.MethodsEDTA-blood samples from 124 adults, 10 adolescents, 13 children and 3 infants were tested in parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Previously, we pointed out GABRB2 and HMGA2 as potential diagnostic makers in thyroid tumors [26]. HMGA2 interacts with the transcription machinery (acts in the chromatin structure and regulates the transcription) and in the epithelial-mesenchymal transition (by repression of E-cadherin) [47, 50, 51]. Although HMGA2 and GABRB2 were not associated with clinical features or somatic alterations in the large-scale expression analysis, the independent validation demonstrated that GABRB2 hypomethylation and overexpression were significantly altered in BRAF V600E tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we pointed out GABRB2 and HMGA2 as potential diagnostic makers in thyroid tumors [26]. HMGA2 interacts with the transcription machinery (acts in the chromatin structure and regulates the transcription) and in the epithelial-mesenchymal transition (by repression of E-cadherin) [47, 50, 51]. Although HMGA2 and GABRB2 were not associated with clinical features or somatic alterations in the large-scale expression analysis, the independent validation demonstrated that GABRB2 hypomethylation and overexpression were significantly altered in BRAF V600E tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Another POC CD4 technology is the EMD Millipore Muse Auto CD4/CD4% system (367,368). This technology replaces the discontinued Guava Auto CD4%/CD4 system.…”
Section: Expansion Of Cd4 Services Using Poc Assaysmentioning
confidence: 99%
“…Until today, two field studies of the Muse Auto CD4/CD4% have been published, both by the same group [18,19]. One study, conducted in the Central African Republic, also looked at analytical performance, and although the number of enrolled patients was smaller than requested by WHO prequalification, and a FACSCount was used as predicate instrument, both precision and bias estimates were within the WHO acceptance criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument requires a laboratory, stable power supply and skilled laboratory personnel but it uses very small amounts of anticoagulated blood (10μL) and reagents, and produces a result within 30–40 minutes. Preliminary field tests of this small flow cytometer have shown very promising results [18,19]. The present study is the first manufacturer-independent study of the Muse Auto CD4/CD4% System in accordance with the WHO protocol for performance evaluation of CD4 technologies in a reference laboratory [20,21].…”
Section: Introductionmentioning
confidence: 99%